Risk Factors for Ovarian Cancer: A Literature Review (Indian Journal of Public Health Research & Development, 2021)
Ovarian cancer is the third type of gynecologic cancer in terms of prevalence after cervical and uterinecancer. The disease is known as the silent killer as it is slowly spread without a diagnosis, which leads tothe worst prognosis and high mortality rate. Libya shows low disease incidence while the high mortalityrate is seen in developed countries due to a lack of proper diagnostic and treatment options. This researchaims to understand the various risk factors of ovarian cancer described in literature. Based on the literaturereview related to various factors which are the demographic, reproductive history, hormonal factors, geneticfactors, lifestyle such as diet and BMI. Various controversial in literature exist on the effect of these factorsand their association with risk factors.
Keywords: Ovarian cancer, Risk factors, conceptual, literature review.